How to Manage Inflammatory Bowel Disease Patients When They Withdraw Anti-Tumour Necrosis Factor [Anti-TNF] Due to Severe Anti-TNF-Induced Skin Lesions? A Multicentre Cohort Study. (26th February 2022) - Cottron, C; Treton, X; Altwegg, R; Reenaers, C; Amiot, A; Fumery, M; Vuitton, L; Peyrin-Biroulet, L; Bouguen, G; Dewit, O; Nancey, S; Caillo, L; et al.
Abstract: Background and Aims: Optimal management of patients with inflammatory bowel disease [IBD] after anti-tumour necrosis factor [TNF] discontinuation due to severe induced skin lesions is unclear. Our study aimed to describe dermatological and IBD evolution after anti-TNF discontinuation for this side effect. Methods: We conducted a multicentre retrospective study including consecutive IBD patients who discontinued anti-TNF due to severe induced skin lesions. Our objectives were to determine factors associated with dermatological remission [complete disappearance of skin lesions] and with IBD relapse in patients with inactive disease at inclusion, notably the impact of an early switch to another biological agent within 3 months of anti-TNF discontinuation. Results: Among the 181 patients [134 women, 160 Crohn's disease] included in the 13 participating centres, dermatological remission occurred in 110 [62%] patients with a median [interquartile range, IQR] interval of 8.0 [6.8–11.0] months. Scalp location was independently associated with less remission of skin lesions (hazard ratio [HR] = 0.64 [95% CI 0.43–0.94], p = 0.02) while early switch was independently associated with a higher probability of remission of skin lesions (HR = 1.64 [95% CI 1.1–2.5], p = 0.02). Among the 148 patients with inactive IBD at inclusion, disease relapse occurred in 75 [51%] patients with a median [IQR] interval of 26.0 [23.0–39.1] months. Survival rates without IBD relapse at 1 year were 85.8% [95% CI 77.5–94.9] in the early switch group and 59.3% [95% CI 48.9–71.9] in the other group [ p < 0.01]. Conclusions: Early switch to a new biological is associated with a higher probability of healing of anti-TNF-induced skin lesions and significantly reduces the risk of IBD relapse.